Do Child Abuse and Maternal Care Interact to Predict Military Sexual Trauma?. Issue 4 (22nd December 2014) - Wilson, Laura C.; Kimbrel, Nathan A.; Meyer, Eric C.; Young, Keith A.; Morissette, Sandra B.
Abstract : Objective: The present research tested the hypothesis that maternal care moderates the relationship between childhood sexual abuse and subsequent military sexual trauma (MST). Method: Measures of childhood sexual abuse, maternal care, and MST were administered to 197 Iraq and Afghanistan war veterans. Results: After accounting for gender, age, and the main effects of maternal care and childhood sexual abuse, the maternal care x childhood sexual abuse interaction was a significant predictor of MST (odds ratio = .28, β = −1.26, 95% confidence intervals of .10, .80). As hypothesized, rates of MST were higher among veterans who reported childhood sexual abuse and low levels of maternal care (43%) compared with veterans who reported childhood sexual abuse and high levels of maternal care (11%). Conclusion: These findings suggest that high levels of maternal care may act as a protective factor against future revictimization among military service members. These findings have the potential to inform both prevention and intervention efforts.